CHARACTERISTIC FEATURES OF THE CLINICAL COURSE OF CHRONIC PARENCHYMAL MUMPS IN CHILDREN DURING EXACERBATION - P.I. Tkachenko; Y.V. Popelo; N.M. Lokhmatova; O.B. Dolenko; S.O. Bilokon; N.M. Korotych; O.V. Dubrovina (Український стоматологічний альманах)
Due to the fact that the etiology and pathogenesis of parenchymal mumps are not well understood, there is an urgent need for further study of individual components of the mechanisms that play a significant role in the manifestation of chronic inflammation in the parotid salivary glands.